The Perceptions of Arabic Language Teachers and Leaders on Student Experience with Digital Learning During the COVID-19 Pandemic - Ghozlan, Abdelfatah (2020)
Background: This study was designed to explore the perceptions of Arabic language teachers and leaders on their students’ experience with digital learning during the COVID-19 Pandemic in three high-performing private schools in Dubai. Methodology: The study adopted a mixed-method approach that utilized a quantitative-qualitative questionnaire and semi-structured interviews for data collection as well as document analysis. Results: Analysis of the questionnaire findings revealed that Arabic teachers shared considerably positive perceptions towards their students’ engagement in digital learning against four of the seven standards of the International Society for Technology in Education (ISTE), namely Empowered learner, Digital citizen, Creative Communicator and Knowledge Constructor. These findings were supported by data obtained from interviews with their Arabic leaders who adapted flexible leadership approaches to facilitate the achievement of these outcomes. However, the Innovative Designer, Computational Thinker and Global Collaborator standards showed less frequency of application by students from the perspective of their teachers and leaders. Despite notable attempts, results indicated that the latter three standards were not substantially reflected in practice before the pandemic, but intensive exposure to digital learning during school closure predicted promising potential for these schools to meet international standards in a relatively short period of time. This remarkable performance of the participating schools can be used as a benchmark for other schools aspiring to unlock the potential of technology in their learners. Therefore, this study analysed the UAE’s Distance Learning Evaluation Tool. Data obtained from this document analysis, along with findings from the questionnaire and interviews, were used to inform the development of Reality-Based Assessment Criteria for digital learning. These criteria were recommended for consideration as a precursor transitional step towards a more sustainable assessment of digital learning. Recommendations: The study recommends practitioners view the ISTE Standards from a progressive and incremental perspective rather than a discrete one. This is because teachers’ responses rated these standards according to the complexity of skills involved in each standard. It also recommends that future research initiatives may conduct predictive analytics of teachers and students’ digital learning aptitudes to envision technology integration after the pandemic.